1998
DOI: 10.1073/pnas.95.10.5584
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane localization is required for RGS4 function in Saccharomyces cerevisiae

Abstract: RGS4, a mammalian GTPase activating protein for G protein ␣ subunits, was identified by its ability to inhibit the pheromone response pathway in Saccharomyces cerevisiae. To define regions of RGS4 necessary for its function in vivo, we assayed mutants for activity in this system. Deletion of the N-terminal 33 aa of RGS4 (⌬1-33) yielded a nonfunctional protein and loss of plasma membrane localization. These functions were restored by addition of a C-terminal membrane-targeting sequence to RGS4 (⌬1-33). Thus, pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
155
2
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(160 citation statements)
references
References 48 publications
(55 reference statements)
2
155
2
1
Order By: Relevance
“…When viewed by fluorescence microscopy, GFP-CTSte18 was localized to the plasma membrane ( Figure 4B), confirming that the last nine amino acids of Ste18p (Table 2) are sufficient to target a heterologous protein to the plasma membrane (Srinivasa et al, 1998). Mutation of the cysteine corresponding to C106 in Ste18p, the thioacylation site, or the residue corresponding to the farnesylation site (equivalent to C107) resulted in a loss of plasma membrane localization, suggesting that both lipid modifications are required for plasma membrane association in the absence of protein-protein interactions with Gpa1p ( Figure 4B).…”
Section: A Prenylation and Thioacylation Motif Is Sufficient For Plasmentioning
confidence: 61%
“…When viewed by fluorescence microscopy, GFP-CTSte18 was localized to the plasma membrane ( Figure 4B), confirming that the last nine amino acids of Ste18p (Table 2) are sufficient to target a heterologous protein to the plasma membrane (Srinivasa et al, 1998). Mutation of the cysteine corresponding to C106 in Ste18p, the thioacylation site, or the residue corresponding to the farnesylation site (equivalent to C107) resulted in a loss of plasma membrane localization, suggesting that both lipid modifications are required for plasma membrane association in the absence of protein-protein interactions with Gpa1p ( Figure 4B).…”
Section: A Prenylation and Thioacylation Motif Is Sufficient For Plasmentioning
confidence: 61%
“…To determine whether αS toxicity is due to membrane binding, two different C-terminal membrane-targeting sequences (mts) that should increase the amount αS on the plasma membrane were tested. Mts1 (SNSVCCTLM) and mts2 (GSGGCCLLS) are derived from the yeast proteins Ste18 and Ras2, respectively; in vivo, these tags are palmitoylated, and the resultant palmitoylated protein localizes to the plasma membrane (16). Cells expressing untagged αS exhibited impaired growth compared with vector control cells, whereas cells expressing αS-mts1 or αS-mts2 exhibited an even more pronounced growth defect than cells expressing the untagged protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8) Similarities among the N-terminal sequences of RGS4, RGS5, and RGS16 (67) suggested that RGS5 and RGS16 may also be N-end rule substrates. This prediction was tested, thus far, with RGS16, and was confirmed.…”
Section: Rgs4 Is An N-end Rule Substratementioning
confidence: 99%
“…The encoded N-terminal sequence of RGS4 is similar to those of RGS5 and RGS16; the similarities include Cys-2 and a basic residue at position 3 (55,67). To test whether RGS16 was an N-end rule substrate, we expressed RGS16 in reticulocyte lysate.…”
Section: Rgs4 Is An N-end Rule Substratementioning
confidence: 99%
See 1 more Smart Citation